Characteristics, Challenges, and Proposals for the Improvement of Short Pre-school Education Programmes in Slovenia : Analysis of Focus Groups (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Our research focuses on the implementation of short pre-school education programmes in Slovenia, intended for children who had not been enrolled in kindergarten in the year prior to entering primary school. The purpose of the study was to recognise the characteristics, challenges, and potential programme improvement proposals. Data obtained through focus groups consisting of professional staff having implemented the short programme in previous years were collected through semi-structured interviews and analysed using qualitative content analysis in the Atlas.ti software. The study reveals a systemic change need in the short programme. The participants highlighted challenges pertaining to access to data on children not enrolled in pre-school education, linguistic and cultural communication barriers and the programme organisation at the level of kindergarten and state level. Only coordinated approaches at all levels - from individual kindergartens to national guidelines - can ensure optimal development and further learning conditions of pre-school children.